2023
DOI: 10.4018/ijcallt.317748
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners' Perceptions and Attitudinal Fluctuations Toward Digital Multimodal Composition

Abstract: This longitudinal study used a mixed-methods approach to investigate multiple digital multimodal composition (DMC) tasks effect on EFL learners' attitudes toward DMC. The sample consisted of Arabic-speaking students (n = 40), enrolled in an English language program at a Saudi university. Data comprised multiple sources, including five online tasks, five questionnaires, reflections, and focus group discussions. The findings show that students maintained positive attitudes toward DMC, suggesting that such attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…This similarity underscores learners' cognizance of the pivotal and communicative role of text, regardless of the writing mode. Previous research has indicated positive attitudes among L2 students toward DMC in terms of interest, meaning-making, communication, and writing development (Alrajhi, 2023a). Such positive views further suggest learners' engagement in this form of composition, which encompasses both nonlinguistic components and textual aspects, including linguistic accuracy.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…This similarity underscores learners' cognizance of the pivotal and communicative role of text, regardless of the writing mode. Previous research has indicated positive attitudes among L2 students toward DMC in terms of interest, meaning-making, communication, and writing development (Alrajhi, 2023a). Such positive views further suggest learners' engagement in this form of composition, which encompasses both nonlinguistic components and textual aspects, including linguistic accuracy.…”
Section: Discussionmentioning
confidence: 88%
“…The qualitative findings highlight learners' engagement and satisfaction with DMW, given its effective communication of meaning (Alrajhi, 2023a). As an enhanced educational experience (Veliz & Hossein, 2020) contributing to effective communication, the learners were intrigued by the utilization of multi-semiotic resources.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation